A bio-physicochemical perspective of the Bay of Bengal. (16th June 2020) - Sarker, Subrata; Panassa, Essowè; Hossain, M. Shahadat; Chowdhury, Sayedur Rahman; Yadav, Atul Kumar; Sharifuzzaman, S.M.
Abstract: Knowledge of bio-physicochemical variables is essential to better understand the functioning of tropical marine ecosystems, which are rich in biodiversity and provide nutrition and livelihoods to billions of people in the developing countries. This study analysed the spatial and temporal variability of phytoplankton and zooplankton with chlorophyll, primary productivity, temperature, salinity, oxygen and nutrients in the Bay of Bengal (BoB), collecting data from the World Ocean, and COPEPOD and Aqua MODIS records. The results indicated a strong gradient in bio-physicochemical conditions of the BoB, from the coast to the open sea. Specifically, the spatial variability in chlorophyll was negatively correlated ( R 2 = 0.59) with temperature and zooplankton, while a positive correlation ( R 2 = 0.70) was noted between chlorophyll and silicate, nitrate, phosphate, dissolved oxygen and salinity. All the variables exhibited a strong vertical gradient at depths up to 500 m. Temperature, nutrients, zooplankton and to a lesser extent salinity and rainfall had an influence on the annual abundance of phytoplankton. Over the long term, a significant positive trend in temperature and a significant negative trend in primary productivity were observed in the BoB. The findings of this study will be useful to draw insights on the state of fisheries habitats and the overall environmental conditions of the BoB in response to future climate changes.